Pengaruh Pelatihan dan Disiplin Kerja Terhadap Produktivitas Kerja Pegawai pada Badan Kepegawaian Daerah (BKD)Kabupaten Bima - Mutiara; Firmansyah Kusumayadi (Indo Publishing, 2025)
This study aims to determine whether training and work discipline have a positive and significant effect on employee work productivity at the Regional Personnel Agency (BKD) of Bima Regency. The instrument in this study used a questionnaire with a Likert scale. The population in this study was 62 employees consisting of 30 Civil Servants, 9 Government Employees with Work Agreements, 16 Honorary employees and 7 volunteer employees. The sample in this study was 39 Civil Servants with the sampling technique used was purposive sampling. Data collection techniques used observation, questionnaires, documentation. Data analysis techniques used validity tests, reliability tests, multiple linear regression tests, classical assumption tests, correlation coefficient tests, determination coefficients, t tests and f tests with the help of SPSS version 26 for Windows. The results of the study indicate that there is a significant partial positive effect of training on employee work productivity, a partial positive and significant effect of work discipline on employee work productivity, and a simultaneous positive and significant effect of training and work discipline on employee work productivity at the Regional Personnel Agency (BKD) of Bima Regency.